Banking Application of the Credit Card Product at Maisarah Window in the Sultanate of Oman: An Analytical Jurisprudence Study: - Alsinani, Said Salim Said (Journal of Islamic Sciences, 2022)
The study aimed primarily at clarifying the ruling on credit card fees with Maisarah, and the extent of their agreement with the legal controls, then the researcher concluded this study by issuing the legal ruling for the credit card product at Maisarah. At the end of the study, the researcher concluded that the credit card product with a soft window is a valid contract that fulfilled the conditions and pillars of the credit card contract, except what included some forbidden conditions- in the researcher’s view- that do not refer to the origin of the product as invalid.